Geomorfologia da zona costeira do sul do Estado de Sergipe - Ramos, Laísa Peixoto (2019)
The coastal zone is an environment that naturally attracts people due mainly to its beauties and natural resources. Because of human occupation, relevant information on geology and geomorphology, such as dunes and mangroves, is being lost. The geomorphological map constitutes an inventory of the aspects of the substrate and the processes that occur in a given region. Thus, the aim of this work was to: (i) refine the existing geological-geomorphological map using remote sensing techniques; (ii) characterize the sedimentary substrate; (iii) make a geomorphological map in the coastal zone of southern Sergipe State. The methodology included: digital image processing, digital terrain model, field work, granulometric and statistics sediment analysis, and geomorphological mapping. From the analysis and integration of the data obtained by the techniques of digital image processing and digital terrain model it was possible to refine, redefine and rename the geomorphological units. The coastal zone of southern Sergipe presents two geomorphological units: coastal tablelands and coastal plain, which are in contact with each other by inactive cliffs. The coastal plain was divided into seven subunits: internal marine terraces, ancient dunes, wetlands/lagoon, external marine terraces, modern dunes/interdunes, tidal flats/mangroves and beaches. Due to the different geomorphological and sedimentological characteristics of the mapped units/subunits, each unit presented a response for digital image processing and the digital terrain model. In the digital image processing it was possible to perceived the differences between: (i) types of vegetation in the study area, especially mangroves; (ii) sites with exposed sandy substrate, such as current dunes and beaches, due to the spectral behavior of the quartz sands; (iii) "clean water" and "suspended sediment water" areas such as wetlands and lagoons, and (iv) alignments and truncations of the inner and outer beach-ridges. The digital terrain model was of special importance to highlight the units with topographical differences, such as coastal tablelands, ancient dunes, and modern dunes. This work pointed the importance of remote sensing and the use of its techniques for the improvement of the geomorphological mapping of coastal zones.